The interrogation style in the poetry of Ibn-Uthaymeen - Al Sharary, Khaled Saleh (Arab Journal for Sciences and Research Publishing, 2016)
This study addressed the interrogation style in the poetry of Ibn-Uthaymeen through his book "Precious Necklace of Ibn-Uthaymeen Poetry", in a scientific way and following a statistical syntactic approach. The study aims to know the different styles of each of interrogative tools that were mentioned in his divan. The study introduced at the beginning the poet Mohammed bin Uthaymeen, who is not the same known Sheikh Mohammed bin Uthaymeen, then defining interrogation idiomatically and linguistically. After that the researcher talked about the interrogative tools and their denotations and meaning. And then he moved to track them in the poetry of Ibn-Uthaymeen, looking into all of his poems and demonstrating to how much they are related to the linguistic contexts: To come to the extent he, the Arabian Peninsula poet Mohammed bin Uthaymeen, was obsessed with using interrogation, and to how much he was committed or not to syntactical rules through the full induction to his poetry.